Glucagon-like peptide-1 receptor agonists and tirzepatide are associated with reduced mortality, cardiovascular, and psychiatric risks in patients with hidradenitis suppurativa and type 2 diabetes and/or obesity: a retrospective cohort study - Inga C. Brouer; Aida Zani; Henning Olbrich; Ralf J. Ludwig; Diamant Thaçi (Frontiers in Medicine, 2026)
Background Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease strongly associated with obesity and diabetes mellitus type 2 (T2D). GLP-1 receptor agonists (GLP-1RAs) and tirzepatide are increasingly used for metabolic control, but their systemic effects in HS remain poorly characterized. Objectives To compare all-cause mortality, cardiovascular, rheumatologic, metabolic, psychiatric, and non-communicable inflammatory outcomes in HS patients with T2D or obesity treated with GLP-1RAs/tirzepatide vs. alternative metabolic medications. Methods This retrospective cohort study used the US Collaborative Network in TriNetX. Adults (≥18 years) with HS and T2D or obesity were included, excluding prior bariatric surgery. Exposed patients received a GLP-1RA or tirzepatide for at least one year, controls received other systemic antidiabetic or anti-obesity agents. Outcomes over a 2-year follow-up were assessed using 1:1 propensity score matching (PSM) for each outcome category. Outcomes included all-cause mortality, cardiovascular, rheumatologic, metabolic, psychiatric, and non-communicable inflammatory events. Hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated, and Cox regression was used to confirm significant findings. Sensitivity analyses and benchmark comparisons were performed. Results Before matching, 8,564 patients received GLP-1RA/tirzepatide and 6,299 alternative therapies. After matching, GLP-1RA/tirzepatide use was associated with reduced all-cause mortality (HR: 0.24, 95% CI: 0.145–0.395; p < 0.0001) and major adverse cardiovascular events (MACE) (HR: 0.61, 95% CI: 0.500–0.749; p < 0.0001). Risks of stroke and heart failure were also reduced (both p < 0.05). Psychiatric outcomes, including depression (HR: 0.78), suicidal ideation (HR: 0.38), and substance use disorder (HR: 0.58), were significantly reduced (all p < 0.05). Risks for rheumatologic and non-communicable chronic inflammatory outcomes were similar among groups. A modest increase in the risk of hyperlipidemia (HR: 1.25), metabolic dysfunction-associated steatotic liver disease (MASLD) (HR: 1.37), and nausea/vomiting (HR: 1.31) was observed in the GLP-1RA/tirzepatide group compared with alternative therapies (all p < 0.05). Conclusion GLP-1RAs and tirzepatide are associated with reduced mortality, cardiovascular and psychiatric morbidity in HS patients with obesity or T2D, without increasing rheumatologic or inflammatory risk. These results extend the systemic benefits of GLP-1RAs and tirzepatide beyond metabolic control and suggest potential therapeutic value in HS.